Strength training in professional soccer: Effects on short-sprint and jump performance - Nuñez, J.; Suarez-Arrones, L.; de Hoyo, M.; Loturco, I. (International Journal of Sports Medicine, 2022)
Several studies have confirmed the efficacy of strength training to maximize soccer player performance during competition. The aim of this meta-analysis was to determine the effects of different strength training protocols on short-sprint and vertical jump performance of professional soccer players from the first division of their countries. The following inclusion criteria were employed for the analysis: (a) randomized studies; (b) high validity and reliability instruments; (c) studies published in a high-quality peer-reviewed journal; (d) studies involving professional soccer players from the first division; (e) studies with descriptions of strength training programs; and (f) studies where countermovement jump and 10-m sprint time were measured pre and post training. Overall, the different strength-oriented training schemes produced similar performance improvements, which seem not to depend on the training strategy. Strength training appears to have a lower effect when applied during in-season than when applied in pre-season periods in first division soccer players. In this meta-analysis it is not possible to confirm that strength training in isolation is capable of improving the short-sprint and jump performance of elite soccer players. The congested fixture schedule and, thus, the limited time to perform complementary (non-specific) training sessions, may contribute to these reduced effects.